Perancangan Sistem Penjualan Self Service Berbasis Web pada Kedai DICAFFE - Fharadilla Rahmah; Hani Setiani; Muhammad Alfarisz; Zaki Satwika Widyadhana; Aries Saifudin (Journal of Research and Publication Innovation, 2023)
Today's business world requires technology that can provide a convenience in its application and use. Kedai DICAFFE is one of the businesses engaged in the fast food and beverage industry at a very affordable price. At this time DICAFFE still uses a cashier system that is served by employees of the shop so that the sales transaction process is hampered and there are still frequent errors in entering menus or payments. With the above problems, researchers apply customer relationship management. The purpose of this research is to present new innovations in the cashier gadget at the DICAFFE shop where the gadget is integrated with the price gateway. This system proposes the theme of self service technology, where transactions are carried out independently by buyers. In developing the system, researchers used PHP and the SDLC method. The resulting output is a website-based self-service cashier system to provide a new experience and increase the competitiveness of coffee shops. With this method, it will make it easier for DICAFFE shops to carry out transactions.